Reasons Why Patients Do Not Return to Sport Post ACLReconstruction: A Cross-Sectional Study - Hamdan M; Haddad BI; Amireh S; Abdel Rahman AMA; Almajali H; Mesmar H; Naum C; Alqawasmi MS; Albandi AM; Alshrouf MA (Journal of Multidisciplinary Healthcare)
Mohammad Hamdan,1 Bassem I Haddad,1 Saadat Amireh,2 Anas Mohammad Ahmad Abdel Rahman,2 Hala Almajali,2 Hazim Mesmar,2 Christina Naum,2 Mahmmud Sameer Alqawasmi,1 Alaa M Albandi,2 Mohammad Ali Alshrouf2,3 1Department of Special Surgery, Division of Orthopedics, School of Medicine, The University of Jordan, Amman, 11942, Jordan; 2School of Medicine, The University of Jordan, Amman, 11942, Jordan; 3Special Accident and Joint Surgery, Sportklinik Hellersen, Lüdenscheid, 58515, GermanyCorrespondence: Mohammad Ali Alshrouf, Special Accident and Joint Surgery, Sportklinik Hellersen, Paulmannshöher Street 17, Lüdenscheid, 58515, Germany, Tel +491622462460, Email M.Alshrouf@outlook.comBackground: Patients who incur an anterior cruciate ligament (ACL) injury and undergo ACL reconstruction (ACLR) have the intention of returning to sports at their pre-injury level; however, many do not return to the pre-injury level. This study aims to investigate the common factors that hinder patients from resuming sports activities following ACLR and to assess how these barriers impact their ability to return to sports. We hypothesized that patients’ psychological factors, including fear of reinjury, would significantly influence their decision to return to sport after ACL reconstruction.Methods: In this cross-sectional study, 138 patients who had undergone ACL reconstruction surgery were examined. The research methodology involved conducting interviews to gather comprehensive data on demographic, psychological, and physical factors that impact the resumption of sports activities following ACLR. The factors considered encompassed knee-related symptoms, life-related reasons, and choice-related reasons, such as fear of reinjury.Results: Among the 138 participants who were included, the mean age was 33.49 ± 9.19 years, with only 39 (28.3%) patients indicated a successful return to their pre-injury activity levels. The obstacles preventing the resumption of sports activities were more commonly attributed to reasons such as fear of reinjury (79.8%) and persistent knee symptoms (78.8%), rather than choice-related reasons (excluding fear of reinjury) (23.2%), such as lack of time or interest, and life-related reasons (18.2%), including work, family, and education. In addition, patients who completed the rehabilitations were 6.277 times more likely to return to the previous level of activity (95% CI 1.801– 21.880; P = 0.001).Conclusion: This research places emphasis on the impact of psychological factors, particularly the fear of reinjury, more commonly in male, on the decision to resume sports activities. In addition, persistent knee symptoms and completion of rehabilitation after ACLR is another factors contributing in returning to sport. Psychological evaluation and counseling may identify those less likely to return to sport, allowing for more targeted interventions to further improve ACLR outcomes.Keywords: anterior cruciate ligament, ACL, rehabilitation outcomes, reconstruction, fear of reinjury, return to sport